Ahamulina n. gen. (Cestoda: Diphyllidea) from the polkadot catshark, Scyliorhinus besnardi (Carcharhiniformes: Scyliorhinidae), off Brazil - Marques, Fernando P. L.; Jensen, Kirsten; Caira, Janine N. (Zootaxa, 2012)
A new genus and species of diphyllidean, Ahamulina catarina n. gen. n. sp., is described from the polkadot catshark, Scyliorhi-nus besnardi, from Santa Catarina, Brazil. The new genus exhibits apical organ armature that is unique among diphyllideans inthe arrangement and shape of the apical hooks as well as in the lack of lateral hooklets. The taxon also exhibits a bipartite cirrussac. This is the seventh diphyllidean reported from a shark, and the third reported from a catshark suggesting that the dearth of cestode data for these particular sharks belies the true extent of diphyllidean diversity they host.